Mark Twain : Young Writer - Mason, Miriam E.; Illustrated by Henry S Gillette (New York : Aladdin Paperbacks, 1991 Aladdin, 1991)
Describes the boyhood of Samuel Clemens in Missouri and how he came to begin a writing career under the pen name Mark Twain.
Include Illustrations
Keywords: Manners and Customs -- Missouri -- Twain, Mark, 1835-1910